Development of a 10-litre pilot scale micro-nano bubble (MNB)-enhanced photocatalytic system for wastewater treatment - Zhao, Mengyu (Environmental technology, 2024)
A 10-litre pilot scale micro-nano bubble (MNB)-enhanced photocatalytic degradation system was developed using ZnO as the photocatalyst and salicylic acid (SA) as the model pollutant. The effectiveness of the MNB/ZnO/UV system was systematically compared with those of MNB, UV, MNB/UV, MNB/ZnO and ZnO/UV degradation systems. The effects of process parameters, including catalyst dosage, pollutant concentration, air-intake rate, pH and salt content on the degradation of SA, were comprehensively investigated. Optimum performance was obtained at neutral conditions with a catalyst dosage of 0.3 g/L and an air-intake rate of 0.1 L/min. For the degradation of SA, a kinetic constant of 0.04126/min was achieved in the MNB/ZnO/UV system, which is 4.5 times greater than that obtained in the conventional ZnO/UV system. The substantial increase in the degradation rate can be attributed to that the air MNB not only enhanced the gas-liquid mass transfer efficiency but also elevated the concentration of dissolved oxygen. A 10-litre pilot scale MNB/ZnO/UV system was successfully applied to the purification of lake water and river water, demonstrating great application potential for wastewater treatment